Ischemic stroke subtype is associated with outcome in thrombolyzed patients. (15th March 2016) - Schmitz, M. L.; Simonsen, C. Z.; Svendsen, M. L.; Larsson, H.; Madsen, M. H.; Mikkelsen, I. K.; Fisher, M.; Johnsen, S. P.; Andersen, G.
Abstract : Objectives: The impact of ischemic stroke subtype on clinical outcome in patients treated with intravenous tissue‐type plasminogen activator (IV‐tPA) is sparsely examined. We studied the association between stroke subtype and clinical outcome in magnetic resonance imaging (MRI)‐evaluated patients treated with IV‐tPA. Material and methods: We conducted a single‐center retrospective analysis of MRI‐selected stroke patients treated with IV‐tPA between 2004 and 2010. The Trial of ORG 10172 in Acute Stroke Treatment criteria were used to establish the stroke subtype by 3 months. The outcomes of interest were a 3‐month modified Rankin Scale score of 0–1 (favorable outcome), and early neurological improvement defined as complete remission of neurological deficit or improvement of ≥4 on the National Institute of Health Stroke Scale at 24 h. The outcomes among stroke subtypes were compared with multivariable logistic regression. Results: Among 557 patients, 202 (36%) had large vessel disease (LVD), 153 (27%) cardioembolic stroke (CE), 109 (20%) small vessel disease, and 93 (17%) were of other or undetermined etiology. Early neurological improvement was present in 313 (56.4%) patients, and 361 (64.8%) patients achieved a favorable outcome. Early neurological improvement and favorable outcome were more likely in CE patients compared with LVD patients (odds ratio (OR), 2.1 (95% confidence interval, 1.4–3.3), and 2.0 (95% confidence interval, 1.2–3.3), respectively). Conclusions: Cardioembolic stroke patients were more likely to achieve early neurological improvement and favorable outcome compared with LVD stroke following MRI‐based IV‐tPA treatment. This finding may reflect a difference in the effect of IV‐tPA among stroke subtypes.